Black Phosphorus–Polymer Composites for Pulsed Lasers. Issue 10 (14th July 2015) - Mu, Haoran; Lin, Shenghuang; Wang, Zhongchi; Xiao, Si; Li, Pengfei; Chen, Yao; Zhang, Han; Bao, Haifeng; Lau, Shu Ping; Pan, Chunxu; Fan, Dianyuan; Bao, Qiaoliang
<x xml:space="preserve">Abstract</x> Black phosphorus (BP) is a very promising material for telecommunication due to its direct bandgap and strong resonant absorption in near‐infrared wavelength range. However, ultrafast nonlinear photonic applications relying on the ultrafast photocarrier dynamics as well as optical nonlinearity in black phosphorus remain unexplored. In this work, nonlinear optical properties of solution exfoliated BP are investigated and the usage of BP as a new saturable absorber for high energy pulse generation in fiber laser is demonstrated. In order to avoid the oxidization and degradation, BP is encapsulated by polymer matrix which is optically transparent in the spectrum range of interest to form a composite. Two fabrication approaches are demonstrated to produce BP‐polymer composite films which are further incorporated into fiber laser cavity as nonlinear media. BP shows very fast carrier dynamics and BP‐polymer composite has a modulation depth of 10.6%. A highly stable Q‐switched pulse generation is achieved and the single pulse energy of 194 nJ is demonstrated. The ease of handling of such black phosphorus‐polymer composite thin films affords new opportunities for wider applications such as optical sensing, signal processing, and light modulation.